Lego DC comics super heroes. Aquaman : rage of Atlantis [videorecording (DVD)] (LEGO DC Comics super heroes, 2018)
Behold Atlantis, a kingdom of wonder and power beneath the ocean's surface and ruled by ranking Justice League member and all-around awesome Atlantean, Aquaman! With his beloved Queen Mera and trusted half-brother Orm by his side, it seems there is nothing that Aquaman cannot conquer. But when the Justice League's Trouble Alert calls, this water dweller heads for dry land and is joined by Batman, Superman, Wonder Woman and rookie Green Lantern, Jessica Cruz. Faced with an extra-terrestrial test that will threaten Earth and even other worlds, Aquaman finds himself a true fish out of water and even a king without a crown! Get ready to dive into an ocean of adventure and laughs in this LEGO movie.